The coordination of the Law degree's final dissertation at the UPF: operation and lessons after two years of experience - Pablo Pareja Alcaraz (Universitat Politècnica de València, 2014)
The goal of this paper is twofold: first, it aims at presenting the operation of the Law Degree's final dissertation at the Universitat Pompeu Fabra; and second, it seeks to analyze the experience accumulated over the past two years and to draw some lessons that - specially with regards to its organization and coordination- may prove helpful to other institutions and universities. After a short introduction, the paper sketches the complex normative framework surrounding the course "Degree's final dissertation" at the Universitat Pompeu Fabra. Following this, the paper describes those constrains and initial considerations that informed its design. This brief analysis provides the necessary context to the following pages, which focus on the several stages the course includes and the main coordination activities attached to them. The paper concludes with a reflection on the main lessons that can be drawn after two years of experience and with some suggestions. Among others, three deserve special attention: first, the need to adopt a flexible, proactive, close, continued and anticipatory style of coordination to ensure the success of the course; second, the convenience to elaborate a course guide as clear and concise as possible; third, the relevance of creating a brief manual that helps professors in their tutorial activities and the ulterior evaluation of papers, particularly in those cases that involve a large number of professors.